Pecularities of the preparation period of high peak performance handball players - Skarbalius, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Sport performance of athletes is predetermined by their training. Correlative relations between training loads and sport performance create a possibility to establish changes of sport performance. It is possible to apply further one metamodel of training and sport performance and to compare it with real sport performance. Restoration of the model may help to understand course of events better. Manifestation of models may be short-term and of longer duration. The problem is that variables of several types act simultaneously. Having analysed loads of one type it is possible to determine metamodel of sport performance only approximately. It is necessary to find the whole table of algorithm. It is more important to find not only short-term metamodel but also mezzo-cycle, macro-cycle. Constant analysis of the load and results enables to manage sport performance seeking that athletes would be of the best sport fitness during the main competition. Thus dynamic models may also exist (Mester, Perl, 2000). Methods One alternative experiments were applied during the period of 1981-2003 seeking to establish peculiarities of specific training programs and efficiency of the preparation period. Data were analyzed by 2x2 repeated measure analysis of variance. Data are presented as means±standard deviation. Data were considered significantly different when the probability was 0.05 or less. Correlation relations have been established by means of Pearson`s correlation coefficient. Results It was established that preparation period of the handball athletes consists of six micro-cycles while preparing for the main competition. It is necessary to train 33-37 days during the said period, to have 48-53 trainings sessions, to play 9-12 matches and to assign 110-120 hours for preparation. Handball athletes most often have one day per week for passive rest. In separate micro-cycles number of working hours varies from five to seven, training sessions - from 5 to 11, number of matches may increase even up to 4-5; sometimes they are training more than 30 hours during the emphasized cycle. Average trainings per week: days - 5,8±0,8, training sessions - 8,3±2,3, played matches - 1,7±0,8; in total it is trained 19,3±6,6 hours, integral training makes 20,4±6,3%, tactical - 13,4±9,4%, technical 22,3±4%, physical - 32,1±16,8%, theoretical - 12,2±14%. After six weeks of training many of sport performance indices of high peak performance handball athletes improve statistically reliably. Indices characterizing physical capacity as well as power and power endurance indices improve most of all. Endurance (3000 m running) improves statistically reliably (p<0,01) in 9,7±3,7%, power endurance (sit-up in 30 seconds) - in 8,5±2,9% (p<0,05), strength-speed (squat jump) - in 9,4±4,1% (p<0,05), speed-strength (counter movement jump) - in 7,7±2,5% (p<0,05), speed endurance (shuttle running) - in 5,9±2,1% (p<0,05). Speed indices change insignificantly: 30-m standing running increase in 3,8±1,9%. Indices of specific activity improve, however not evenly: the dribbling of 30-m long distance from standing position and after taking run more quickly accordingly in 4,6±1,8% and in 4,8±1,9%. Catching and passing the ball improves in 4,1±2,1%. All these indices improve, however statistically not significant. Agility changes more significantly - in 7,2±2,2% (p<0,05). Discussion/Conclusion Having estimated impact of sport performance indices on competition activity it was established that agility abilities had not a great impact on efficiency of attack shots (r=0,109). There were very week relations with other indices of competition activity (mistakes, taken over balls, blocking of shots, penalties, efficiency of goalkeepers` playing). Endurance indices have an essential relation with a number of attacks (r=0,555) and counterattacks (r=0,499). Such research results allow drawing a conclusion, that interaction skills of team athletes and tactical performance as well as a game concept has more significance on the quality of handball game. Thus upon improving physical performance of the handball athletes during the preparatory period it is necessary to improve competition experience simultaneously. So in this period it is very important to find competitors of adequate level of sport performance or even stronger in order team players could acquire interaction skills playing in high speed and under great competitive ability. Direct impact of insufficient competitive activity on insufficient sport performance established by tests, coincides with results of other researchers proving that sport result is determined by training specificity (Bangsbo, 1994; Müller, 2001).